Some Topical Issues of Teaching and Practical Implementation of Management in Higher Education - Ossik, Yuriy; Shakhshina, Ainur (Naše gospodarstvo/Our economy, 2013)
This paper reviewed actual questions that, for some reason, are often not reflected upon in the modern course of management—namely, the discussion of the directi- on of society’s socio-economic activity, the ratio of management and ethics, and the ratio of quantity and quality of work of managers and workers in the context of the development of new branches of economic science (i.e., happiness economics).